Peritoneal fetus and tubal placentation: A case report of an abdominal pregnancy - Singh, Alka; Sharma, Paban (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> Reported here is a silent case of an abdominal pregnancy with fetal demise at twenty one weeks gestation, extracted from the peritoneal cavity at laparotomy along with the removal of placenta contained in fallopian tube by salphingectomy without any effort. Key words: intra-uterine fetal demise, abdominal fetus, placenta doi:10.3126/njog.v2i1.1479 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 56 - 58 May -June 2007